Can ear and soft-biometric traits assist in recognition of newborn? - Tiwari S.; Singh A.; Singh S.K. (My University, 2025)
Missing, swapping, mixing, and illegal adoption of newborns is a global challenge and research done to solve this issue is minimal and least reported in the literature. Most of the biometric systems developed are for adults and very few of them address the issue of newborn identification.The ear of newborn is a perfect source of data for passive identification of newborn as they are the highly non cooperative users of biometrics. The four characteristics of ear biometrics: universality, uniqueness, permanence and collectability make it a very potential biometric trait for the identification of newborn. Further the use of soft-biometric data like gender, blood group, height and weight along with ear enhances the accuracy for identification of newborn. The objective of this paper is to demonstrate the concept of using ear and soft-biometrics recognition for identification of newborn. The main contribution of the research are (a) the preparation of ear and soft biometric database of newborn. (b)Fusion of ear and soft-biometrics data for identification of 210 newborn, results in an improvement of approximately 5.59% over the primary biometric system i.e. ear. © 2012 Springer-Verlag GmbH.